Core Set of Domains for Outcome Measures in Behçet's Syndrome. Issue 4 (4th March 2022) - Hatemi, Gülen; Meara, Alexa; Özgüler, Yesim; Direskeneli, Haner; Mahr, Alfred; Shea, Beverly; Cam, Esen; Gul, Ahmet; Yazici, Yusuf; Tugwell, Peter; Yazici, Hasan; Merkel, Peter A.; et al.
Abstract : Objective: An unmet need exists for reliable, validated, and widely‐accepted outcome measures for randomized clinical trials in Behçet's syndrome. The Outcome Measures in Rheumatology (OMERACT) Behçet's Syndrome Working Group, a large, multidisciplinary group of experts in Behçet's syndrome and patients with Behçet's syndrome, had an objective of developing a core set of data‐driven outcome measures for use in all clinical trials of Behçet's syndrome. Methods: The core domain set was developed through a comprehensive, iterative, multistage project that included a systematic review, a focus group meeting and qualitative patient interviews, a survey among experts in Behçet's syndrome, a Delphi exercise involving both patients and physician experts in Behçet's syndrome, and use of the data, insight, and feedback generated by these processes to develop a final core domain set. Results: All steps were completed and domains were delineated across the organ systems involved in this disease. Since trials in Behçet's syndrome often focus on specific manifestations and not on the disease in its entirety, the final proposed core set includes 5 domains mandatory for study in all trials in Behçet's syndrome (disease activity, new organ involvement, quality of life, adverse events, and death) with additional subdomains mandatory for study of specific organ–systems. The final core set was endorsed at the 2018 OMERACT meeting. Conclusion: The core set of domains in Behçet's syndrome provides the foundation through which the international research community, including clinical investigators, patients, the biopharmaceutical industry, and government regulatory bodies can harmonize the study of this complex disease, compare findings across studies, and advance development of effective therapies.